Revision of the genus Sadoletus Distant, with description of new species from China and Australia (Hemiptera: Heteroptera: Heterogastridae) - Gao, Cuiqing; Malipatil, M.b. (Zootaxa, 2019)
The species of genus Sadoletus are revised based on re-examination of the type material. A total of eighteen species are recognized in this genus, including five new species: Sadoletus abathonotus sp. nov., Sadoletus alphus sp. nov., Sadoletus biprotuberans sp. nov., and Sadoletus planus sp. nov. from China, and Sadoletus variabilis sp. nov. as the first representative of the genus from Australia, described in the present contribution. The following new subjective synonymy is proposed: Sadoletus validus Distant, 1903 = Sadoletus subpellucidus Ban, 2018 syn. nov. Sadoletus valdezi as treated in Ban & Ishikawa (2013) is proved to be a misidentification, now correctly described as Sadoletus planus sp. nov.. Three species, Sadoletus validus Distant, 1903, Sadoletus voluptarius Bergroth, 1918, Sadoletus melasmus Ban, 2018 are newly recorded from China. A key to all the known species of Sadoletus is provided. The lectotypes and paralectotypes are designated for S. validus Distant, 1903, S. pallescens Distant, 1909, S. valdezi Bergroth, 1918, S. voluptarius Bergroth, 1918, S. montanellus Bergroth, 1918 and S. montivagus Bergroth, 1918. Based on external and genitalia morphology, two “species groups” have been recognized amongst the species described in this genus until now. The main group, including 14 of the 18 known species, is confirmed as the typical Sadoletus (with type-species S. validus), for which a redefinition is provided. However the generic placement of the remaining four species is unclear at present, hence are tentatively retained under the present genus Sadoletus, pending further investigation involving other related heterogastrid genera, and using both morphological and molecular data.